The Kinsey Institute : The First Seventy Years - Allen, Judith A., 1955- (Book collections on Project MUSE., 2017)
An in-depth history of Alfred Kinsey's groundbreaking Institute for Sex Research and the cultural awakening it inspired in America-"it has no rival" (Angus McLaren). While teaching a course on Marriage and Family at Indiana University, biologist Alfred Kinsey noticed a surprising dearth of scientific literature on human sexuality. He immediately began conducting his own research into this important yet neglected field of inquiry, and in 1947, founded the Institute for Sex Research as a firewall against those who opposed his work on moral grounds. His frank and dispassionate research shocked America with the hidden truths of our own sex lives, and his two groundbreaking reports -Sexual Behavior in the Human Male (1948) and Sexual Behavior in the Human Female (1953)-both became New York Times bestsellers. In The Kinsey Institute: The First Seventy Years, Judith A. Allen and her coauthors provide an in-depth history of Kinsey's groundbreaking work and explore how the Institute has continued to make an impact on our culture. Covering the early years of the Institute through the "Sexual Revolution," into the AIDS pandemic of the Reagan era, and on into the "internet hook-up" culture of today, the book illuminates the Institute's enduring importance to society.